2017
DOI: 10.3390/md15070216
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterols from Dunaliella tertiolecta Reduce Cell Proliferation in Sheep Fed Flaxseed during Post Partum

Abstract: The post partum period is characterized by immunosuppression and increased disease susceptibility. Both phytosterols from microalga Dunaniella tertiolecta and dietary supplementation with n-3 polyunsaturated fatty acids (PUFA) influence cell proliferation and cytokine release during inflammation. The objective of this paper was the evaluation of the effects of physterols, extracted and purified from D. tertiolecta, on the in vitro immune responses of ewes supplemented with flaxseed during post partum. Twenty C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
8
2
Order By: Relevance
“…Recently, the anti-proliferative role of the two main phytosterols (7-dehydroporiferasterol and ergosterol) extracted and purified from D. tertiolecta was thoroughly studied on sheep PBMCs [11]. Similar inhibitory results of phytosterols from D. tertiolecta in sheep PBMCs during the postpartum period were found [10]. The immunological effects of phytosterols on cell proliferation are associated with their chemical structure; in particular, sterol components can relieve chronic gastric ulcers in a rat model [28], a mouse skin cancer model, and HT29 colon adenocarcinoma [29,30].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Recently, the anti-proliferative role of the two main phytosterols (7-dehydroporiferasterol and ergosterol) extracted and purified from D. tertiolecta was thoroughly studied on sheep PBMCs [11]. Similar inhibitory results of phytosterols from D. tertiolecta in sheep PBMCs during the postpartum period were found [10]. The immunological effects of phytosterols on cell proliferation are associated with their chemical structure; in particular, sterol components can relieve chronic gastric ulcers in a rat model [28], a mouse skin cancer model, and HT29 colon adenocarcinoma [29,30].…”
Section: Discussionmentioning
confidence: 79%
“…This mitigates excessive inflammation [39]. Moreover, PBMCs from sheep fed a diet rich in ω-3 and subsequently treated in vitro with phytosterols from D. tertiolecta had a main role exerted by ω-3 in driving cytokine production [10]. Conversely, sheep PBMCs treated with a mixture of ergosterol and 7-dehydroporiferasterol from D. tertiolecta had decreasing levels of IL-6 and TNF-α and an increased level of IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some studies, phytosterols and the total lipid fraction isolated from microalgae are identified as responsible for an anti-inflammatory activity due to an increase of anti-inflammatory cytokines and decrease of pro-inflammatory cytokines secretion. Therefore, their use in animal feed could control immune responses during inflammation and minimize the use of antibiotics [128,129]. These biological activities make them useful in the cosmetic sector.…”
Section: Sterol Lipidsmentioning
confidence: 99%